The motor neuron response to SMN1 deficiency in spinal muscular atrophy. Issue 5 (May 2014) - Kang, Peter B.; Gooch, Clifton L.; McDermott, Michael P.; Darras, Basil T.; Finkel, Richard S.; Yang, Michele L.; Sproule, Douglas M.; Chung, Wendy K.; Kaufmann, Petra; de, Darryl C.; ,
ABSTRACT Introduction: The purpose of this study was to measure and analyze motor unit number estimation (MUNE) values longitudinally in spinal muscular atrophy (SMA). Methods: Sixty‐two children with SMA types 2 and 3 were observed prospectively for up to 42 months. Longitudinal electrophysiological data were collected, including compound motor action potential (CMAP), single motor unit action potential (SMUP), and MUNE. Results: Significant motor neuron loss and compensatory collateral reinnervation were noted at baseline. Over time, there was a significant mean increase in MUNE (4.92 units/year, P = 0.009), a mean decrease in SMUP amplitude (−6.32 μV/year, P = 0.10), and stable CMAP amplitude. Conclusions: The unexpected longitudinal results differ from findings in amyotrophic lateral sclerosis studies, perhaps indicating that compensatory processes in SMA involve new motor unit development. A better understanding of the mechanisms of motor unit decline and compensation in SMA is important for assessing novel therapeutic strategies and for providing key insights into disease pathophysiology. Muscle Nerve49: 636–644, 2014